Coming Closer? Tax Morale, Deterrence and Social Learning after German Unification - Benno Torgler
The paper explores whether a social learning model helps explain the observed conformity and compliance with social norms after the unification of Germany. We compare tax morale, (the willingness to pay taxes), between inhabitants of East and West Germany during the post-unification period, using three World Values Survey/European Values Survey waves between 1990 and 1999. German unification is of particular interest in analysing tax morale since it is close to a quasi-natural experiment. Factors such as a common language, similar education systems and a shared cultural and political history prior to the separation after the Second World War can be controlled because they are similar. Our findings indicate that the social learning model employed in this study helps to predict the development of tax morale over time. It is clear that tax morale values converged within a mere nine years after unification, due largely to a strong change in the level of tax morale in the East. Thus, the paper contributes to the literature that attempts to explain how norms arise, how they are maintained and how they are changed.Tax Morale, Social Learning, Conformity, Convergence Process, Deterrence, Quasi-Natural Experiment